Galectins regulate the inflammatory response in airway epithelial cells exposed to microbial neuraminidase by modulating the expression of SOCS1 and RIG1() - Nita-Lazar, Mihai (Mol Immunol, 2015)
Influenza patients frequently display increased susceptibility to Streptococcus pneumoniae co-infection and sepsis, the prevalent cause of mortality during influenza pandemics, but the detailed mechanisms by which an influenza infection predisposes patients to suffer pneumococcal pneumonia is not fully understood. A murine model for influenza infection closely reflects the observations in human patients, since if the animals that have recovered from influenza A virus (IAV) sublethal infection are challenged with S. pneumoniae, they undergo a usually fatal uncontrolled cytokine response. We have previously demonstrated both in vitro and in vivo that the expression and secretion of galectin-1 (Gal1) and galectin-3 (Gal3) are modulated during IAV infection, and that the viral neuraminidase unmasks galactosyl moieties in the airway epithelia. In this study we demonstrate in vitro that the binding of secreted Gal1 and Gal3 to the epithelial cell surface modulates the expression of SOCS1 and RIG1, and activation of ERK, AKT or JAK/STAT1 signaling pathways, leading to a disregulated expression and release of pro-inflammatory cytokines. Our results suggest that the activity of the viral and pneumococcal neuraminidases on the surface of the airway epithelial cells function as a “danger signal” that leads to rapid upregulation of SOCS1 expression to prevent an uncontrolled inflammatory response. The binding of extracellular Gal1 or Gal3 to the galactosyl moieties unmasked on the surface of airway epithelial cells can either “fine-tune” or severely disregulate this process, respectively, the latter potentially leading to hypercytokinemia.